The evaluation of formula 100 utilization program towards the nutrtitional status of malnourished children after treatment - Riska Mayangsari; Madarina Julia; Susetyowati Susetyowati (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2018)
ABSTRAKLatar belakang: Persentase balita kurus di Kabupaten Muna sebesar 11,8% dan balita sangat kurus sebanyak 6,3%. Sesuai rekomendasi World Health Organization (WHO), perbaikan status gizi balita gizi buruk dilakukan dengan memperbaiki asupan zat gizi dengan memberikan formula terapi berupa pemberian Formula 100 (F-100), dimana F-100 merupakan makanan yang berbahan dasar susu yang diberikan pada fase transisi dan fase rehabilitasi Tujuan:Mengetahui daya terima F-100 oleh balita gizi buruk dan mengetahui hubungan daya terima F-100 balita gizi buruk dengan perubahan status gizi.Metode:Jenis penelitian ini merupakan penelitian observasional yang menggunakan rancangan kohort prospektif. Sampel penelitian adalah seluruh balita umur 12-24 bulan yang mengalami gizi buruk berjumlah 73 balita yang telah memenuhi criteria inklusi dan eksklusi.Sampel penelitian mendapatkan F-100 selama 5 minggu.Analisis data yang digunakan adalah univariat dan bivariat. Hasil:Sebagian besar subjek (63,08%) termasuk dalam kategori daya terima baik dengan menghabiskan F-100 yang diberikan dan sisanya (36,92%) termasuk dalam kategori daya terima kurang dengan tidak menghabiskan F-100 yang diberikan. Hasil uji Chi Square menunjukan ada hubungan antara daya terima F-100 dengan perubahan status gizi (p=0,02) (RR=2,7, 95% CI=1,07-7,21). Kesimpulan :Terdapat hubungan yang signifikan antara daya terima F-100 denganperubahan status gizibalita (p<0,05). KATA KUNCI: evaluasi, status gizi, F-100ABSTRACTBackground: The total percentage of underweight children in Muna District was 11.8% and the percentage of severe wasted children was 6.3%. As recommended by World Health Organization (WHO),improvement in nutritional status of malnourished children is conductedby improving food supplementation. Giving therapeutic formula 100 (F-100), where F-100 is the food made from dairy products which given in transition and rehabilitation phase. Objectives:To figure out the admission of F-100 by malnourished children and to find out the correlation between F-100 admission from malnourished children and the changing of nutritional status. Methods: This research is an observational study using the design of prospective cohort study. The sample were the whole children aged 12-24 months who suffered malnutrition with the total number up to 73 children who have fulfilled the criteria of inclusion and exclusion. The study sample had received F-100 for 5 weeks. The data analysis used is univariate and bivariate.Results: Most of the subjects are included in the category of well admission (63.08%) by spending given F-100 and the rests are included in the category of less admission (36.92%) by not spending the given F-100. The result of Chi Square Test shows that there is correlation between the admission of F-100 andthe changing of nutritional status (p=0.02) (RR=2.7, 95% CI=1.07-2).Conclusions: There is significant correlation between the admission of F-100 and the changing of children’s nutritional status (p<0.05)KEYWORDS: evaluation, status, nutrition, F-100